2019
DOI: 10.1038/s41385-019-0163-3
|View full text |Cite
|
Sign up to set email alerts
|

Platelet activating factor receptor regulates colitis-induced pulmonary inflammation through the NLRP3 inflammasome

Abstract: Inflammatory bowel disease (IBD) is a progressive disease that includes Crohn's diseases and ulcerative colitis. Over one third of IBD patients have secondary organ pathologies and pulmonary manifestations are common. The platelet activating factor receptor (PAFR) plays a critical role in regulating inflammation and it is expressed on epithelial cells and neutrophils in both colon and lung. Having identified increased expression of PAFR in both the gastrointestinal (GI) tract and lungs of mice with dextran sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 53 publications
3
44
0
Order By: Relevance
“…Antibiotic‐mediated microbiome depletion increased susceptibility of mice to an experimental lung infection, and FMT improved pathogen clearance and lung function in antibiotic‐treated mice 73 . Many studies also show that lung inflammation is observed in different models of experimental colitis in mice 74,75 . However, it remains unclear how changes in the composition of the gut microbiome translate to pathophysiologic effects in the lung.…”
Section: Nlrp3 Inflammasome In Gut–lung Cross Talkmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibiotic‐mediated microbiome depletion increased susceptibility of mice to an experimental lung infection, and FMT improved pathogen clearance and lung function in antibiotic‐treated mice 73 . Many studies also show that lung inflammation is observed in different models of experimental colitis in mice 74,75 . However, it remains unclear how changes in the composition of the gut microbiome translate to pathophysiologic effects in the lung.…”
Section: Nlrp3 Inflammasome In Gut–lung Cross Talkmentioning
confidence: 99%
“…It is possible that these PRRs also assist bacterial translocation from gut to lung tissues. A recent study showed that Ptafr levels are increased in the lungs of mice with experimental colitis 75 . Pharmacologic inhibition of Ptafr reduces Nlrp3 inflammasome activation and lung inflammation in the colitis model 75 .…”
Section: Nlrp3 Inflammasome In Gut–lung Cross Talkmentioning
confidence: 99%
“…BMDMs were stained with single color and unstained cells were also used as controls for analysis. Data was analysed using FlowJo software (BD Biosciences, Franklin Lakes, USA) as previously described [26,27].…”
Section: Flow Cytometrymentioning
confidence: 99%
“…Classically activated macrophages participate in key proinflammatory responses and enhance antigen presentation and pathogen clearance (Imai et al, 2018;Valderrama and Nizet, 2018;Hafner et al, 2019). IL-1β is a neutrophil recruitment factor produced by macrophages and DCs upon exposure to GAS (Valderrama et al, 2017;Flaherty et al, 2018;Liu et al, 2019). Recent research has discovered that an optimal level of IL-1β must be produced to eliminate pathogens and avoid excessive tissue lesion formation and mortality (Castiglia et al, 2016;Flaherty et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…PAF serves as a phospholipid mediator manufactured by endothelial cells, neutrophils, macrophages, and granular eosinophils (Chaithra et al, 2018). PAF mediates IL-1β-induced chemotaxis of natural killer cells and neutrophilsand can induce the migration of neutrophils to infection sites (Liu et al, 2019). Liu et al reported the protective effect of Sse immunization against skin infection with M1 strain MGAS5005 (Liu et al, 2007), a hypervirulent CovS mutant.…”
Section: Introductionmentioning
confidence: 99%